O conceito de federalismo no pensamento político de Proudhon - Tomasi, Matildes Regina Pizzio (2018)
This research is constituted in the study of the Federalism concept, based on the premises of Pierre-Joseph Proudhon, French anarchist thinker. It has as a goal to understand the concept of the Federalism in the Proudhon thought, considering its elaboration in the 19th century. The methodology is based on a literature review, prioritizing works that have within the studied concept: Federalism. As well as the immersion in the historic time lived by Proudhon (France of the 19th century), comprehending the theoric-methodologic and descriptive dimension, embracing the history of Ideias, of Concepts and Theory of Political Thought. We recognize the Federalism as a political and economic system anti-State and anti-Capitalist, based on concepts of reciprocity and equality, constituted by the equilibrium between liberty and authority. The Federalism decentralizes the power, abolishes the State, emancipates the communes, provinces, communities. It installs horizontal and autonomous relationship between the mutualist unities that go interconnecting forming networks of interdependence, with no external, vertical and dominating intervention. The Federalism establishes peace between nations by being based on liberty and authority of all federate territories, being recognized as one of the founding principles of the Anarchism.